Dietary restraint and weight loss in relation to disinhibited eating in obese Veterans following a behavioral weight loss intervention. (1st September 2019) - Dochat, Cara; Godfrey, Kathryn M.; Golshan, Shahrokh; Cuneo, Jessica Gundy; Afari, Niloofar
Abstract: Ability to restrain one's dietary intake is a necessary skill for weight loss. However, dietary restraint has been shown to paradoxically increase disinhibited eating in certain populations, thereby negatively impacting weight loss and leading to worse overall health outcomes. The aim of this study was to address gaps in the literature regarding the relationships between separate facets of dietary restraint (intention; behavior) with weight loss and various types of disinhibited eating (binge eating, external eating, emotional eating) in overweight and obese adults who recently completed a weight loss intervention. A sample of mostly male Veterans with overweight and obesity ( N = 88) self-reported their dietary restraint intention, restraint behavior, and current disinhibited eating following completion of an 8-week behavioral weight loss treatment. Greater dietary restraint intention was related to greater dietary restraint behavior, p < .05. Greater dietary restraint behavior was significantly related to greater recent weight loss, p < .05, while restraint intention was not, p > .05. Greater dietary restraint intention was related to greater current binge eating and external eating, while greater self-reported restraint behavior was related to less binge eating, p < .05. Thus, dietary restraint behavior appears to be adaptive for this population, whereas rigid dietary restraint intention may increase risk for disinhibited eating. To decrease disinhibited eating and improve weight loss outcomes in Veterans, interventions might specifically address rigid rule-following associated with abandonment of weight loss goals and help Veterans develop specific yet flexible eating plans. Future research should examine whether dietary restraint intention and behavior differentially predict disinhibited eating and weight loss outcomes prospectively.